Study on regulators of purifying magnesite ore by cationic reverse flotation - Pengcheng Li (Nature Portfolio, 2021)
Abstract The floatability of magnesite, dolomite and quartz is a major factor affecting the removal of silicon and calcium from magnesite ore. The effect of the regulators sodium hexametaphosphate (SH), sodium silicate (SS), trisodium phosphate (TP), tannic acid (TN) and monoammonium oxalate (OA) on the floatability of magnesite, dolomite, and quartz under the ether amine (EAH) system was studied. The results show that the five regulators have relatively little influence on the floatability of quartz and magnesite. Dolomite can be activated when the dosage of SH is less than 40 mg/L; however, dolomite can be inhibited when the SH dosage is greater than 40 mg/L. The other four regulators have inhibitory effects on dolomite, and TN and TP have strong inhibitory effects on dolomite. Under the conditions of optimum grinding fineness, pH and collector dosage, a recovery of approximately 70% and a concentrate with a grade of over 47% were obtained by three stages of reverse flotation using sodium hexametaphosphate and water glass as regulators and Haicheng magnesite ore with an SiO2 content of 2.38% and a CaO content of 0.75%. Potentiometric measurements and infrared spectroscopy analysis show that physical adsorption occurs between the three minerals and collectors, while the interaction of magnesite and dolomite with SH and SS involves both physical adsorption and chemical adsorption.